SANKSI PIDANA TERKAIT DENGAN PUTUSAN NO.890/PID.SUS/2022/PN.JKT.BRT.: Juridical Review of Criminal Sanctions related to Decisions Number 890/Pid.Sus/2022/Pn. Jkt. Brt. - Silawati Dayang Ganjar; Dian Adriawan Daeng Tawang (Faculty of Law, Universitas Trisakti, 2025)
Cyber law is regulated in the ITE Law. Still, the criminal sanctions it regulates are often imposed much lighter than the maximum penalty threatened, such as the Borobudur Temple Stupa meme case in Decision No. 890/Pid.Sus/2022/PN.Jkt.Brt. Identification of the problems that will be researched, namely: what caused the judge to impose a lighter criminal sanction than the ITE Law regulation in Decision Number 890/Pid.Sus/2022/PN.Jkt.Brt.? And, is the criminal sanction in Decision Number 890/Pid.Sus/2022/PN.Jkt.Brt. in accordance with the purpose of punishment? The research method used is normative research, descriptive in nature, using secondary data through literature study, and qualitative data analysis. The research result and conclusion of the research shows that the judge imposed a lighter criminal sanction because the defendant did not have the intention to commit an act that caused hatred or hostility as regulated in Article 28 paragraph (2) jo. Article 45 of the ITE Law. This lighter criminal sanction is not in accordance with the 3R+1H punishment objectives, namely: Reformation, Restraint, Retribution, and Deterrence. The panel of judges should impose a heavier punishment based on the principles of justice, legal certainty, and expediency to achieve the objectives of punishment.